Implementasi Penggunaan Exam Browser di SMA Negeri 1 Seputih Banyak Lampung - Maulidya, Ade (Wacana Publik, 2025)
Exam browsers are an important part of the world of education in the current era of technological development. This requires changes and developments in the world of learning, including evaluation in education. Therefore, this research aims to determine the purpose, positive and negative impacts of using the exam browser at SMA Negeri 1 Seputih Banyak Lampung. This type of research is descriptive with a qualitative approach. The results show that: the use of exam browsers in the world of education is very impactful and beneficial in the implementation of exams, because the implementation of exam browsers is able to minimize cheating during exams. Then using the exam browser is considered useful, saving costs and time. Researchers advise schools to prepare carefully regarding the implementation of the exam browser so that if there are technical problems they can implement alternative policies during the exam.